2009
DOI: 10.1016/j.aprim.2009.01.014
|View full text |Cite
|
Sign up to set email alerts
|

¿Qué características de los estudiantes de medicina se relacionan con mejores conocimientos y actitudes hacia la medicina de familia?

Abstract: Females and younger student are the ones who demonstrate more favourable attitudes towards family medicine and primary health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
5
2
Order By: Relevance
“…The authors concluded that FM continues to be not well known among Spanish medical students, difficulting that this specialty becomes a viable choice for postgraduate study 10. Recently, Escobar-Rabadán et al surveyed 88 medical students at the beginning and end of a course on primary care 11. The objective of the study was to explore what socio-demographic and academic variables of medical students are associated with a better knowledge and more favourable attitude to FM.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors concluded that FM continues to be not well known among Spanish medical students, difficulting that this specialty becomes a viable choice for postgraduate study 10. Recently, Escobar-Rabadán et al surveyed 88 medical students at the beginning and end of a course on primary care 11. The objective of the study was to explore what socio-demographic and academic variables of medical students are associated with a better knowledge and more favourable attitude to FM.…”
Section: Introductionmentioning
confidence: 99%
“…In general, students see themselves as family doctors or hospital specialists from the moment they enter the medical school. Different studies have shown that, although there is a margin for variation in the selection of the future specialty, the preferred choice at the moment of entering medical school is a key predictive factor 11 26…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations